2018
DOI: 10.1007/s13202-018-0577-6
|View full text |Cite|
|
Sign up to set email alerts
|

Aptian–Albian shale oil unconventional system as registration of Cretaceous oceanic anoxic sub-events in the southern Tethys (Bir M’Cherga basin, Tunisia)

Abstract: The Bir M'Cherga basin (North-east Tunisia), with about 600 km 2 area, had recorded four Middle Cretaceous source rocks well stratigraphically correlated with the four known oceanic anoxic sub-events: OAE1a, OAE1b, OAE1c, and OAE1d. Variety of lithology, thickness and organic richness had characterized these source rocks. The sedimentary tectonic analysis, the petrology and geochemistry study established the petroleum system of these source rocks. Basin formation began early in the Barremian-Aptian interval by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…The first recognition of the OAE 1d (the Breistroffer level) was by Bréhéret () based on geochemical evaluation of upper Albian sediments of the Vocontian Basin, southern France, having an overall total organic carbon (TOC) content of 1–2 wt%. Further studies confirmed the global distribution of the OAE 1d subevents; for instance, studies from the northwestern Tethys (in the Vocontian Basin, SE France, Bornemann et al, ; Bréhéret, ; Giorgioni et al, ; and in the Pialli Italian Apennines, Coccioni, ), the southern Tethys (in Tunisia, Ben Fadhel, Layeb, Hedfi, & Ben Youssef, ; Talbi, Lakhdar, Smati, Spiller, & Levey, ), the northwestern Atlantic (in Blake Nose Plateau, Watkins, Cooper, & Wilson, ; Wilson & Norris, ), the United States (Scott, Formolo, Rush, Owens, & Oboh‐Ikuenobe, ), and southwestern Venezuela (Rodríguez‐Cuicas, Montero‐Serrano, & Garbán, ). Generally, the OAE 1d is characterized by: (a) a low to moderate positive carbon excursion (0.5–2‰; Bornemann et al, ; Watkins et al, ; Wilson & Norris, ) and TOC contents (1–2 wt%; Bornemann et al, ; Bréhéret, , ; Rodríguez‐Cuicas et al, ); and (b) being a product of stratification collapse in the water column especially in the western tropical Atlantic (Wilson & Norris, ).…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…The first recognition of the OAE 1d (the Breistroffer level) was by Bréhéret () based on geochemical evaluation of upper Albian sediments of the Vocontian Basin, southern France, having an overall total organic carbon (TOC) content of 1–2 wt%. Further studies confirmed the global distribution of the OAE 1d subevents; for instance, studies from the northwestern Tethys (in the Vocontian Basin, SE France, Bornemann et al, ; Bréhéret, ; Giorgioni et al, ; and in the Pialli Italian Apennines, Coccioni, ), the southern Tethys (in Tunisia, Ben Fadhel, Layeb, Hedfi, & Ben Youssef, ; Talbi, Lakhdar, Smati, Spiller, & Levey, ), the northwestern Atlantic (in Blake Nose Plateau, Watkins, Cooper, & Wilson, ; Wilson & Norris, ), the United States (Scott, Formolo, Rush, Owens, & Oboh‐Ikuenobe, ), and southwestern Venezuela (Rodríguez‐Cuicas, Montero‐Serrano, & Garbán, ). Generally, the OAE 1d is characterized by: (a) a low to moderate positive carbon excursion (0.5–2‰; Bornemann et al, ; Watkins et al, ; Wilson & Norris, ) and TOC contents (1–2 wt%; Bornemann et al, ; Bréhéret, , ; Rodríguez‐Cuicas et al, ); and (b) being a product of stratification collapse in the water column especially in the western tropical Atlantic (Wilson & Norris, ).…”
Section: Introductionmentioning
confidence: 74%
“…The reported OAE 1d within the upper part of the Kharita Formation can be correlated with the Mouelha black shale Member from northern Tunisia (Ben Fadhel et al, ), where the former authors identified the OAE 1d based on organic matter‐enrichment (TOC content between 1.8 and 2.44 wt%). To the northwest of Tunisia, Talbi et al () focused their study on the geochemical and petroleum potentiality of the four subevents of OAE 1. They indicated that OAE 1d was dominated by a high TOC content averaged by 2.02 wt%, except for one section that had 13.91 wt% TOC content, which the authors attributed to reworking of Triassic TOC‐rich outcrop.…”
Section: Discussionmentioning
confidence: 99%
“…Since the pioneer work by Burollet (1956), Dubourdieu (1956) andM'Rabet (1981), the stratigraphy and sedimentology of the Hameima Fm and its equivalents have been studied by Chihaoui (2009), Chihaoui et al (2010) andBen Chaabane et al (2019), based on the ammonite biostratigraphic framework by Latil (2011). The Lower Fahdene Fm and its equivalent have been mainly studied for biostratigraphic purposes (Vila et al 1995;Zghal et al 1997;Chihaoui et al 2010;Latil 2011;Ben Fadhel et al 2014), for potential source-rocks analyses (Khalifa et al 2018;Talbi et al 2019) or for synsedimentary tectonics (e.g. Martinez et al 1991;Arfaoui et al 2011;Jaillard et al 2013;Masrouhi et al 2014).…”
Section: Geological Setting and Previous Workmentioning
confidence: 99%